The protection and recovery strategy development of dynamic resilience analysis and cost consideration in the infrastructure network. Issue 1 (2nd February 2022) - Su, Yi-Zhu; Yeh, Wei-Chang
Abstract: Modern life is becoming more and more convenient, all because of the perfect operation of the infrastructure network. However, if these infrastructure networks encounter interference, the operation of the network system will be delayed or even shut down, often causing huge losses in livelihood, economy, and society. Therefore, how to evaluate the resilience of the network system and provide protection and recovery strategies to deal with attacks that interfere with the system are important issues. This study considers a situation with protection, attack, and recovery strategies, proposes the time-related Binary-Addition Tree-based Resilience Assessment to consider more decision variables and parameters, and further includes the costs in the formulation of the protection and recovery strategies. Moreover, a new performance measure oriented to the degree of network reliability recovery to quantify the resilience of the network system is developed. Graphical Abstract: Abstract : Time-related BAT-RA (t-BAT-RA) is developed based on binary-addition tree algorithm-based resilience assessment (BAT-RA). t-BAT-RA considers protection, attack, and recovery strategies with variables formulation and resiliece and cost computation to provide a complete network resilience analysis process for decision-making.